2003
DOI: 10.1029/2002ja009543
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric electron heating, optical emissions, and striations induced by powerful HF radio waves at high latitudes: Aspect angle dependence

Abstract: [1] In recent years, large electron temperature increases of 300% (3000 K above background) caused by powerful HF-radio wave injection have been observed during nighttime using the EISCAT incoherent scatter radar near Tromsø in northern Norway. In a case study we examine the spatial structure of the modified region. The electron heating is accompanied by ion heating of about 100 degrees and magnetic field-aligned measurements show ion outflows increasing with height up to 300 m s À1 at 582 km. The electron den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
166
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 174 publications
(188 citation statements)
references
References 64 publications
18
166
1
3
Order By: Relevance
“…If the pump HF radio waves propagate sufficiently close to parallel to Earth's magnetic field B, the waves can be trapped, thereby depositing most of the HF energy in the plasma (Gurevich et al, 2001). Observations which confirm this prediction were made simultaneously at EISCAT/HEATING facility at Tromsø (Leyser et al, 2000;Kosch et al, 2002;Rietveld et al, 2003) and HAARP (Pedersen and Gurevich et al, 2002;Pedersen et al, 2003). This strong enhancement of trapped HF waves near parallel to B, leading to the magnetic zenith effect, has since been studied at these and other HF facilities.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…If the pump HF radio waves propagate sufficiently close to parallel to Earth's magnetic field B, the waves can be trapped, thereby depositing most of the HF energy in the plasma (Gurevich et al, 2001). Observations which confirm this prediction were made simultaneously at EISCAT/HEATING facility at Tromsø (Leyser et al, 2000;Kosch et al, 2002;Rietveld et al, 2003) and HAARP (Pedersen and Gurevich et al, 2002;Pedersen et al, 2003). This strong enhancement of trapped HF waves near parallel to B, leading to the magnetic zenith effect, has since been studied at these and other HF facilities.…”
Section: Discussionmentioning
confidence: 95%
“…The generation of strong Langmuir turbulence with upper hybrid waves as the primary source of Langmuir waves has been proposed by Mishin et al (2004), who has shown an extended strong-turbulence region. Rietveld et al (2003) have shown that in the course of EISCAT/HEATING experiments, where both the HF pump beam and the UHF radar beam were scanned in elevation between magnetic zenith and vertical directions, the heating effects, such as large electron temperature increases, intense AFAIs, and HF-induced optical emission, all maximized during HF pumping towards MZ. They also showed that large electron temperature increases of 3000 K above the background were accompanied by ion heating of about 100 K, and electron density decreases of up to 20%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations